On The High-Frequency Quasi-Periodic Oscillations From Black Holes - Erkut, Mehmet Hakan (Iop Publishing Ltd, Temple Circus, Temple Way, Bristol Bs1 6Be, England, 2011)
We apply the global mode analysis, which has been recently developed for the modeling of kHz quasi-periodic oscillations (QPOs) from neutron stars, to the inner region of an accretion disk around a rotating black hole. Within a pseudo-Newtonian approach that keeps the ratio of the radial epicyclic frequency kappa to the orbital frequency Omega the same as the corresponding ratio for a Kerr black hole, we determine the innermost disk region where the hydrodynamic modes grow in amplitude. We find that the radiation flux emerging from the inner disk has the highest values within the same region. Using the flux-weighted averages of the frequency bands over this region we identify the growing modes with highest frequency branches Omega+kappa and Omega to be the plausible candidates for the high-frequency QPO pairs observed in black hole systems. The observed frequency ratio around 1.5 can therefore be understood naturally in terms of the global free oscillations in the innermost region of a viscous accretion disk around a black hole without invoking a particular resonance to produce black hole QPOs. Although the frequency ratio <Omega+kappa >/ is found to be not sensitive to the black hole's spin which is good for explaining the high-frequency QPOs, it may work as a limited diagnostic of the spin parameter to distinguish black holes with very large spin from the slowly rotating ones. Within our model we estimate the frequency ratio of a high-frequency QPO pair to be greater than 1.5 if the black hole is a slow rotator. For fast rotating black holes, we expect the same ratio to be less than 1.5.
Keywords: accretion; accretion disks; black hole physics; stars: oscillations; X-rays: stars; x-ray binaries; neutron-stars; power spectra; gro j1655-40; high state; diskoseismology; behavior; region; büyüme; toplanma diskleri; kara delik fiziği; yıldız: salınımlar; X-ışınları: yıldız; X-ışın çiftleri; XTE j1550-564; nötron-yıldız; güç spektrumu; davranış; bölge